Catamenial pneumothorax (Revista Argentina de Cirugía, 2021)
Catamenial pneumothorax is of rare presentation. Its clinical course is variable, and it usually recurs. Wepresent a case of a 35 year-old patient with five episodes of pneumothorax previously treated in anotherinstitution. Videothoracoscopy was used for diagnosis and treatment, which included a diaphragmaticplication followed by pleurodesis. The anatomopathology confirmed the diagnosis. Postoperative curse was uneventful up to date. Catamenial etiology should be considered in all recurrent pneumothoraxoccurring in women with menstrual periods.
Keywords: pneumothorax; catamenial; videothoracoscopy